2001
DOI: 10.1093/jn/131.11.2843
|View full text |Cite
|
Sign up to set email alerts
|

Severity of Human Immunodeficiency Virus Infection Is Associated with Decreased Phase Angle, Fat Mass and Body Cell Mass in Adults with Pulmonary Tuberculosis Infection in Uganda

Abstract: Although coinfection with tuberculosis and human immunodeficiency virus (HIV) is emerging as a major problem in many developing countries, nutritional status has not been well characterized in adults with tuberculosis and HIV infection. We compared nutritional status between 261 HIV-positive and 278 HIV-negative adults with pulmonary tuberculosis in Kampala, Uganda, using anthropometry and bioelectrical impedance analysis. Among 163 HIV-positive and 199 HIV-negative men, intracellular water-to-extracellular wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
85
2
7

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 74 publications
(102 citation statements)
references
References 25 publications
8
85
2
7
Order By: Relevance
“…One major consideration is that TBinfected subjects are expected to have lower baseline BMI and FM than those who are TB uninfected. In studies of Wasting in adults with tuberculosis E Villamor et al TB þ /HIVÀ African adults with pulmonary TB (Shah et al, 2001;Van Lettow et al, 2004), including ours, the typical average BMI is around 18-19 kg/m 2 in both men and women. Also, fat percent is usually o8% in men and 20-24% in women, compared to E15 and E31% in TBuninfected men and women from other African settings (Kotler et al, 1999).…”
Section: Discussionmentioning
confidence: 49%
See 4 more Smart Citations
“…One major consideration is that TBinfected subjects are expected to have lower baseline BMI and FM than those who are TB uninfected. In studies of Wasting in adults with tuberculosis E Villamor et al TB þ /HIVÀ African adults with pulmonary TB (Shah et al, 2001;Van Lettow et al, 2004), including ours, the typical average BMI is around 18-19 kg/m 2 in both men and women. Also, fat percent is usually o8% in men and 20-24% in women, compared to E15 and E31% in TBuninfected men and women from other African settings (Kotler et al, 1999).…”
Section: Discussionmentioning
confidence: 49%
“…Results on the additional impact of HIV on wasting at these low levels of fat percent in TB-infected subjects are inconsistent. HIV infection was related to lower BMI in some (Niyongabo et al, 1994(Niyongabo et al, , 1999Kennedy et al, 1996) but not all (Shah et al, 2001;Madebo et al, 2003;Van Lettow et al, 2004) these previous studies. We did not find associations between HIV and anthropometric indicators of FM such as BMI or TSF; however, we found that HIV infection was associated with decreased indicators of lean mass such as the AMC, in both men and women.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations